2018
DOI: 10.1177/1744806918808150
|View full text |Cite
|
Sign up to set email alerts
|

CD11b-activated Src signal attenuates neuroinflammatory pain by orchestrating inflammatory and anti-inflammatory cytokines in microglia

Abstract: Neuroinflammation plays an important role in the induction and maintenance of chronic pain. Orchestra of pattern-recognition receptor-induced pro-inflammatory and anti-inflammatory cytokines is critical for inflammation homeostasis. CD11b on macrophages could inhibit toll-like receptor (TLR) activation-induced inflammatory responses. However, the function of CD11b on microglia remains unknown. In the current study, we demonstrated that CD11b-deficient microglia cells produced more inflammatory cytokines, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
(80 reference statements)
2
11
0
Order By: Relevance
“…Because a heterogeneous population has been transplanted to hydrocephalic hyh mice, more than one effect is expected. In this way, 10% of MSC were positive for CD11b, a molecule that inhibits TLR-induced inflammatory responses by the inhibition of inflammatory cytokines (IL-6 and TNFα) and increasing anti-inflammatory cytokine (IL-10 and TGF-β) production in microglia [56]. This suggests that part of the transplanted cells could have an anti-inflammatory role.…”
Section: Neuroprotective Effect Of Bm-msc In Hydrocephalic Micementioning
confidence: 95%
“…Because a heterogeneous population has been transplanted to hydrocephalic hyh mice, more than one effect is expected. In this way, 10% of MSC were positive for CD11b, a molecule that inhibits TLR-induced inflammatory responses by the inhibition of inflammatory cytokines (IL-6 and TNFα) and increasing anti-inflammatory cytokine (IL-10 and TGF-β) production in microglia [56]. This suggests that part of the transplanted cells could have an anti-inflammatory role.…”
Section: Neuroprotective Effect Of Bm-msc In Hydrocephalic Micementioning
confidence: 95%
“…Similarly, immunoblotting analyses reveled no differences in extracellular signal-regulated kinase (ERK) activation (phosphorylation) between WT and MPO KO PMNs (Supplemental Figure 2D). ERK plays an important role in PMN chemotaxis (28) and can be activated downstream of CD11b (29).…”
Section: Cd11b Surface Expression Is Not Altered By the Absence Of Mpomentioning
confidence: 99%
“…Our results indicate that the expression of CD11b was weaker than Iba1 ( Figure 7 and Figure 8 ), which led to the subsequent dominance of Iba1+/CD11b− microglial cells in alcoholics in both gray and white matter in SNpr and SNpc (up to 40–50% of all microglial/macrophage population). Previous studies in mice-brain-derived microglial cells have demonstrated that CD11b silences TLR4 (toll-like receptor 4) -induced inflammatory responses [ 89 ]. Such physiological silencing in controls (wild-type mice) leads to increased microglial production of IL-10 and TGF-β (anti-inflammatory cytokines), coupled with decreased production of IL-6 and TNF-α (pro-inflammatory cytokines) [ 89 ], thereby indicating that silencing of CD11b promotes a pro-inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%